Exploring factors that full-service school teachers believe disable their self-efficacy to teach in an inclusive education system - Van Staden-Payne, Isabel; Nel, Mirna (Frontiers in Education, 2023)
Teachers’ sense of self-efficacy has been identified by research as a key factor in the successful implementation of inclusive education. This article reports on disabling factors in South Africa that are reportedly influencing inclusive Full-Service school (FSS) teachers’ sense of self-efficacy to implement inclusive education successfully. A qualitative study, using semi-structured individual and group interviews as well as collages, was employed. The findings revealed that the disabling factors included internal and external factors. Internal factors comprised a lack of knowledge and skills, including a lack of self-confidence, FSS teachers seeing themselves as a barrier, and physical and psychological problems. External factors were also identified. They are ineffective implementation of inclusive education, inadequate training, incompetent education department officials and managers, a lack of support from the education department, curriculum constraints, as well as disabling factors within the school system. Negative media perceptions were also mentioned. It was concluded that it is important for the basic and higher education departments of education to be aware of the identified disabling factors and purposefully attempt to improve the external factors, while ensuring that FSS teachers’ capabilities are developed and sustained in in-service and pre-service teacher education. This could contribute to developing and improving their sense of self-efficacy.